Strategy Formulation and Organizational Performance in Dynamic Real Estate Markets: Evidence from Kenya - Erastus Mwanjama , Katani; Jackson Kivui , Maalu (Multidisciplinary Journal of Technical University of Mombasa, 2025)
This paper empirically examines how strategy formulation influences organizational performance among real estate developers operating in Kenya’s turbulent and institutionally evolving markets. Grounded in the resource-based view, contingency, and dynamic-capabilities perspectives, the study tests a multidimensional framework incorporating environmental dynamics, strategic awareness and institutional support, and engagement. A census of 88 corporate members of the Kenya Property Developers Association (KPDA) was undertaken using a structured questionnaire analysed through multiple regression, moderated and mediated regression (PROCESS v 4.3), and multivariate analysis of covariance (MANCOVA). Results demonstrate that strategy formulation exerts a significant positive effect on organizational performance (β = 0.412, p < 0.001). Environmental dynamics significantly moderate this relationship (β = –0.203, p = 0.017), indicating that the strength of strategic influence diminishes under high turbulence. Strategic awareness and institutional support mediate the link between formulation and performance (indirect effect = 0.186, 95 % CI [0.072, 0.314]), while institutional engagement shows a direct positive effect (β = 0.337, p < 0.010). The overall model explains 68.9 % of variance in performance (R² = 0.689, F (5, 82) = 36.32, p < 0.001). MANCOVA tests confirm significant multivariate effects for role, organization type, and development focus (Wilks’ Λ = 0.558, F (1, 78) = 98.38, p < 0.001). Findings validate the complementarity of deliberate strategic planning, adaptive learning, and institutional connectivity. They extend strategic-management theory to emerging-market property sectors and provide a replicable, statistically robust blueprint for evaluating strategy–performance relationships under environmental turbulence.
Keywords: Strategy formulation, Environmental dynamics, Institutional engagement, Moderated mediation, Organizational performance, Real estate development, Kenya